HBR's 10 Must Reads on Leading Digital Transformation - Review, Harvard (Ascent Audio, 2021)
Become a digital-first organization. If you read (or listen) to nothing else on leading digital transformation, listen to these ten articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help revitalize your offerings and processes, stay ahead of disruptors and technology shifts, and manage the necessary cultural change. This book will inspire you to: minimize disruption while transforming your company; manage the cultural change of adopting new technologies; practice discovery-driven transformation; develop digital intelligence in your workforce; compete in the age of AI; make big changes with an incremental approach; and understand when radical change is needed-and when it isn't.